2020
DOI: 10.1063/5.0004919
|View full text |Cite
|
Sign up to set email alerts
|

Wurtzite quantum well structures under high pressure

Abstract: Quantum well systems based on semiconductors with the wurtzite crystalline structure have found widespread applications in photonics and optoelectronic devices, such as light-emitting diodes, laser diodes, or single-photon emitters. In these structures, the radiative recombination processes can be affected by (i) the presence of strain and polarization-induced electric fields, (ii) quantum well thickness fluctuations and blurring of a well–barrier interface, and (iii) the presence of dislocations and native po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…The calculated results for narrow QWs are in good agreement with the experimental data. However, for wider QWs there are discrepancies between the calculated low oscillator strengths and higher experimental decay rate [69]. The experimentally observed decay, which is too high compared to the calculations, could be due to the screening of the electric field by free carriers.…”
Section: Gan/aln Qwscontrasting
confidence: 58%
See 2 more Smart Citations
“…The calculated results for narrow QWs are in good agreement with the experimental data. However, for wider QWs there are discrepancies between the calculated low oscillator strengths and higher experimental decay rate [69]. The experimentally observed decay, which is too high compared to the calculations, could be due to the screening of the electric field by free carriers.…”
Section: Gan/aln Qwscontrasting
confidence: 58%
“…High-pressure studies, which often combine experiment and theory, can provide important results that are difficult or impossible to obtain otherwise and allow for the description of the main factors that influence radiative recombination processes and radiative efficiency. Recent studies [69,70] have shown that high pressure spectroscopy is an effective tool for analyzing factors related to strain effects, built-in electric fields, and the involvement of defect states in recombination processes in quantum heterostructures. Now we will focus on the built-in electric field (approaching a few MV/cm) present in the polar wurtzite structure of nitride heterostructures.…”
Section: Quantum Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Polarization-induced electric fields can manifest in nanometer-size heterostructures (quantum wells, wires or dots [ 7 , 8 , 9 , 10 ]) and cause a shift of the transition energy between quantum states which is known as quantum-confined Stark effect (QCSE) [ 11 , 12 ]. In some cases, polarization has a beneficial influence on the device performance, e.g., in field effect transistors (FETs) [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in optoelectronic devices, such as light-emitting diodes (LEDs) or laser diodes (LDs), the QCSE should be reduced as much as possible. Associated with the spectral shift, there is a separation of electrons and holes within the structure, which reduces the overlap of electron/hole wavefunctions and consequently the radiative recombination rate and the emission efficiency [ 9 , 10 , 11 , 12 , 16 , 17 ]. The majority of nitride-based optoelectronic devices are based on polar multi-quantum wells (MQWs), with heterointerfaces perpendicular to the polarization axis, so that polarization effects are particularly strong.…”
Section: Introductionmentioning
confidence: 99%